Conhecimento de gestantes quanto ao parto humanizado: intervenção educativa - SOARES, Milene Neves (2019)
In Brazil, the model of obstetric care is characterized by excessive labor intervention, which has contributed to the increase in cesarean, maternal and perinatal rates morbidity and mortality. In fact, about 25 years ago an international movement began to improve the quality of the interaction between parturient and their caregivers, in addition to worrying about suppressing harmful technology. The movement has several denominations in many countries; in Brazil it is called the humanization of childbirth. In 2016, the Ministry of Health developed the National Guideline of Assistance to the Normal Birth that systematically evaluates and updates the scientific information already available with the intention of promoting, protecting and encouraging vaginal delivery. Related to health education in this process, in all stages of the pregnancy-puerperal cycle is extremely important, so it is during prenatal care that women should be better oriented so they can experience birth in a beneficial, confident, fewer risks of complications in the puerperium and a most successful breastfeeding. Health professionals must take the position of educators, sharing knowledge, seeking to give back to women their self-confidence to live the gestation. This study aims to describe the knowledge about humanized childbirth and good obstetrical practices, according to the definition described by the Ministry of Health for pregnant women attending prenatal UMS Icoaraci-PA. The methodology we adopted was an action-research type, with quantitative approach of descriptive character in which 94 pregnant women participated. The survey data were collected through a semi-structured questionnaire with closed questions, after the collection was carried out educational action on good obstetrical practices. The results showed a good knowledge of the participants about the Rights of the pregnant woman, interventions in the prepartum, to accelerate the delivery and postpartum. As for the answers about the definition of humanized childbirth by Ministry of Health, found out that no pregnant woman could provide a complete response in accordance with the conception provided. However, we realize that even though they do not know how to conceptualize humanized labor, most of them know and recognize the practices that are beneficial to them and their babies. Concerning the behaviors considered to be inadequate, we found that a large part of the practices that were routinely used or misused by professionals were perceived negatively, for example measures to accelerate labor, such as amniotomy, Kristeller's maneuver, oxytocin and episiotomy. However, we are struck by the high percentage of these responses that are still considered appropriate even though their uses are considered inadequate or restricted by the Ministries of Health, this happened in some cases, such as episiotomy, intestinal lavage and Kristeller. Demonstrating that needs to be done a lot to change paradigms in order to provide a truly humanized deliveries.